Producer price inflation connectedness and input-output networks - N. Melisa Bilgin; Kamil Yılmaz (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
We analyze the transmission of producer price in inflation shocks across the U.S. manufacturing industries from 1947 to 2018 using the Diebold-Yilmaz Connectedness Index framework, which fully utilizes the information in generalized variance decompositions from vector autoregressions. The results show that the system-wide connectedness of the input-output network Granger-causes the producer price inflation connectedness across industries. The input-output network and the inflation connectedness nexus is stronger during periods of major supply-side shocks, such as the global oil and metal price hikes, and weaker during periods of aggregate demand shocks, such as the Volcker disinflation of 1981-84 and the Great Recession of 2008. These findings are consistent with Acemoglu et al. (2016)'s conjecture that supply shocks are transmitted downstream, whereas demand shocks are transmitted upstream. Finally, preliminary results show that Trump tariffs caused an increase in the system-wide inflation connectedness in the first half of 2018, due to shocks mostly transmitted from tariff-targeted industries, namely, basic metals, fabricated metals and machinery.
Keywords: E3; D57; C32; 330; Input-output networks; Inflation; Connectedness; Supply-side shocks; Commodity prices; Business cycles; Vector autoregression; Variance decomposition